Pengembangan Modul Sistem Kontrol Terprogram untuk Sekolah Menengah Kejuruan - Abdul Hanif; Habibullah Habibullah (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Programmed Control Systems subject is a subject that must be studied by Industrial Automation Engineering students. In the implementation of learning, there is a lack of handbook modules for students, so that low student motivation has an impact on student learning outcomes. The availability of teaching materials will certainly increase student motivation and make it easier to understand lessons both independently and under teacher observation. For this reason, this study aims to produce a valid and practical learning module on the subject of Programmatic Control Systems at SMK Negeri 2 Payakumbuh. This type of research is research with development (Research and Development) using the 4D model which consists of 4 stages, namely the definition stage (Define), the design stage (Design), the development stage (Develop) and the stage of deployment (Disseminate). The subject of this research is a programmed control system learning module using the CX-Programmer software, with respondents from expert lecturers in the electrical engineering department of the Padang State University and class XI TOI teachers in Programmatic Control System (SKT) subjects at SMK Negeri 2 Payakumbuh in the academic year. 2019/2020. Data were collected using sheets or questionnaires for validation and practicality. Based on the results of the validation, the average of the four validators is 91.1% with the very valid category. Respondents from two subject teachers on the practicality of the learning module obtained an average of 90.55% with the very practical category. It was concluded that the programmed control system learning module using the CX-Programmer software was declared valid and practically used in the teaching and learning process for programmed control system subjects